The Brazilian version of the Health-Related Quality of Life Questionnaire for Nausea and Vomiting of Pregnancy: translation, cross-cultural adaptation and reliability – an observational cross-sectional study - Piccini, Adriana (2021)
BACKGROUND: The Health-Related Quality of Life Questionnaire for Nausea and Vomiting of Pregnancy (NVPQOL) is a validated questionnaire assessing quality of life among pregnant women with nausea and vomiting. OBJECTIVE: To translate, cross-culturally adapt and evaluate the reliability of the NVPQOL. DESIGN AND SETTING: Observational cross-sectional study developed in a public university in Brazil. METHODS: The translation, synthesis of translations, back-translation, expert committee, pre-testing and validation were carried out, resulting in a Portuguese-language version. The internal consistency, intra-rater and test-retest reliability and correlation between the total score of the Portuguese-language version of the NVPQOL and the domains of the World Health Organization Quality of Life-bref questionnaire were considered in the data analysis. RESULTS: The instrument went through the process with testing on 104 pregnant women. Strong internal consistency (Cronbach’s α: 0.95), strong intra-rater and test-retest reliability (P < 0.0; intraclass correlation coefficient: 0.89; confidence interval: 0.791-0.945) and strong correlation between the total score of the Portuguese-language version of the NVPQOL and the physical health domain of the World Health Organi- zation Quality of Life-bref questionnaire (P < 0.01; R = -0.8) were observed. CONCLUSION: The NVPQOL was translated, cross-culturally adapted and validated for the Portuguese language with satisfactory psychometric properties for assessing quality of life, especially in relation to physical health, among pregnant women with symptoms of nausea and vomiting in the first trimester of pregnancy.